Construction of a database to identify Staphylococcus species. Issue 3 (March 1989) - Geary, C; Stevens, M; Sneath, P H; Mitchell, C J
Abstract : A database was constructed for the routine identification of Staphylococcus species, isolated from man. The method comprised 15 conventional characterisation tests using substrates incorporated into agar plates and a multipoint inoculation system. The database was constructed from results of 125 reference strains and 1567 clinical isolates. In an evaluation trial, using a probability profile index generated from the database, 529 of 559 (94.6%) further clinical isolates were identified to species level. A further 20 (3.6%) gave low discrimination between two species. The proposed scheme was rapid, reliable, and inexpensive.